Microglial activation occurs late during preclinical Alzheimer's disease - Streit, Wolfgang J.; Braak, Heiko; Del Tredici, Kelly; Leyh, Judith; Lier, Julia; Khoshbouei, Habibeh; Eisenlöffel, Christian; Müller, Wolf; Bechmann, Ingo (Glia, 2018)
Sporadic Alzheimer's disease (AD) is marked by a lengthy preclinical phase during which patients are nonsymptomatic but show pathology in variable manifestations. Whether or not neuroinflammation occurs in such nondemented individuals is unknown. We evaluated the medial temporal lobe of 66 nondemented subjects, aged 42–93, in terms of tau pathology, Aβ deposition, and microglial activation. We show that 100% of subjects had neurofibrillary degeneration (NFD), 35% had Aβ deposits, and 8% revealed microglial activation in individuals where early amyloid formation was apparent by Congo Red staining. Amyloid‐induced neuroinflammatory clusters of Iba1, CD68, and ferritin‐positive microglia were evident in the immediate vicinity of aggregated Aβ. Microglia in the adjacent neuropil were nonactivated. Thus, neuroinflammation in AD represents a highly localized phagocyte reaction, essentially a foreign body response, geared toward removal of insoluble Aβ. Because clustered microglia in some amyloid plaques were dystrophic and ferritin‐positive, we hypothesize that these cells were exhausted by their attempts to remove the aggregated, insoluble Aβ. Our findings show that the sequence of pathologic events in AD begins with tau pathology, followed by Aβ deposition, and then by microglial activation. Because only 8% of our subjects revealed all three hallmark pathologic features, we propose that these nondemented individuals were near the threshold of transitioning from nonsymptomatic to symptomatic disease. The onset of neuroinflammation in AD may thus represent a tipping point in AD pathogenesis. Our study suggests that the role of microglia in AD pathogenesis entails primarily the attempted removal of potentially toxic, extracellular material. Main Points Microglial activation is triggered when Aβ protein aggregates and forms insoluble amyloid. Microglial activation is restricted to the immediate vicinity of amyloid. Amyloid‐induced neuroinflammation may lead to microglial exhaustion and dystrophy.